Analysis of The Effect of Motivation, Discipline and Job Satisfaction, on Employee Performance With Organizational Commitment As An Intervening Variable - Imam Abu Jahid; I Made Adnyana (Ridwan Institute, 2021)
The purpose of this research are to analysis effect of motivation, job satisfaction, employee performance, organizational commitment, 125 sample were selected by random sampling. Data were collected by questionnaires and Structural Equation Model (SEM) were applies as an analysis technique. The results analysis showed that the variables of Motivation, Job Satisfaction have a positive and significant effect on Employee Performance through Organizational Commitment